Pembelajaran Wawasan Siaga Bencana Kepada Masyarakat Dusun Bajulmati Desa Gajahrejo Kecamatan Gedangan Kabupaten Malang - Sulaiman, Mochamad; Handoko, Puji; Pujiarsih, Pujiarsih (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
Bajulmati Backwoods is one of four backwoods under the auspices of Gajahrejo Village which has extraordinary natural potential. However, the low level of public knowledge about the concern to preserve the environment can have a detrimental impact. The detrimental impact can be seen from the magnitude of the potential disaster that has occurred in the last 10 years, such as the annual flood disaster. So on this basis, the need for PPM activities related to how to cope with disasters also prevents disasters. The disaster preparedness activity received a very positive response from the community, so that this activity could be achieved well and smoothly. In the future, the community still needs follow-up efforts and assistance to further develop the existing natural and environmental potential.